Core of Medicine - Misrah (Stimulus: A Medical Humanities Journal, 2023)
The drawing depicts the art of medicine by signifying the importance of the heart, which is the center of human being. With an influence of art that plays a role when it comes to diagnosing to patient and having to use different instruments and medium when achieving a goal.